Penanaman Akhlak di Era Modern - Akhyar, Aidil; Sofian, Sophan; Zamzami, Makky (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
In this research, instilling moral values ​​is the main part in forming a person with noble character. The practice of noble morals is the main part in making people believers and devoted to Allah SWT. Morals have a broad scope and lead humans to achieve happiness in this world and in the afterlife. The research method used in this research is qualitative methods. Data collection techniques were carried out through collecting supporting references in this research manuscript. Morals are the main pillar in creating a society that has a high value of obedience to Allah SWT. Morals have important values ​​in everyday life. If you want to make society's life better, of course you need to have morals that are embedded and practiced well. instilling moral values ​​also motivates students to develop themselves according to their interests and talents. Islam not only talks about worship, but also about social life, including the development of science and technology, so Islam has comprehensive coverage of all existing aspects. Morals are the main thing in directing individuals to behave in daily activities.